Investigating food allergy awareness and attitudes among teachers in primary schools: current status and opportunities for enhancement - Amal H. Aljohani; Abeer Mutair Alshamani; Afnan Ahmed Aljohani; Aisha Saad Almohammadi; Bushra Saad Alharbi; Deena Faraj Altarjami; Reyouf Samer Alsaedi (Frontiers in Pediatrics)
BackgroundFood allergies are common among children worldwide. This occurs when the immune system has an abnormal reaction to certain foods. This reaction can range in severity from mild to severe and may lead to anaphylaxis, which can be fatal. As teachers are the first responders in managing such situations in schools, this study aims to explore and measure primary school teachers' knowledge and attitudes about food allergies and their management and review the current school policy.MethodsThis cross-sectional study uses a randomly distributed online questionnaire to measure teachers' knowledge and attitudes at primary schools in Medina, Saudi Arabia.ResultsThe sample consisted of 383 primary school teachers. Approximately 87.5% of the participants were aware of food allergies. More than two-thirds of teachers were able to identify anaphylactic shock. Only 15.4% of the teachers knew that an epinephrine autoinjector was the first aid measurement to be taken. Additionally, 39.9% of the teachers reported that the school does not have an action plan for dealing with students with food allergies. Approximately 93.4% of the participants agreed that avoiding foods that cause allergies is important for preventing allergies.ConclusionsThis study revealed teachers' good knowledge in the identification of food allergy and their symptoms, as well as the awareness of their potential severity. However, the study highlighted a significant gap in management. Most had positive attitudes toward learning about food allergies. Therefore, administration policies and strategies need to be implemented to assist in managing food allergies at school.